ANALISIS KEMAMPUAN LITERASI MEMBACA SISWA DI SDN 29 RANTAU BATU PASAR - Putri, Dinda Oktavia; Elvina, Elvina (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
One of the fundamental skills that significantly determines students' future learning success is reading literacy. Reading literacy is not only defined as the ability to recognize letters or words, but also encompasses understanding, interpretation, analysis, and the ability to connect information from texts with existing knowledge. This study aims to analyze the reading literacy skills of students at SDN 29 Rantau Batu Pasar, literacy development efforts, and the inhibiting factors that influence them. The research method used was qualitative with a descriptive approach. Data were collected through observation, interviews, and documentation with teachers, students, the principal, and parents. The results showed that most students had literacy skills at the elementary to secondary level, with a small number still experiencing difficulties. Inhibiting factors included low reading interest, limited reading materials, and a lack of variety in learning methods. This study concluded that improving reading literacy can be achieved through the provision of reading facilities, parental involvement, and the use of innovative learning methods.